Optimization of cutting parameters based on surface roughness and assistance of workpiece surface temperature in turning process - Suhail, Adeel H.; Ismail, Napsiah; Wong, Shaw Voon; Abdul Jalil, Nawal Aswan (Science Publications, 2010)
Problem statement: In machining operation, the quality of surface finish is an important requirement for many turned workpieces. Thus, the choice of optimized cutting parameters is very important for controlling the required surface quality. Approach: The focus of present experimental study is to optimize the cutting parameters using two performance measures, workpiece surface temperature and surface roughness. Optimal cutting parameters for each performance measure were obtained employing Taguchi techniques. The orthogonal array, signal to noise ratio and analysis of variance were employed to study the performance characteristics in turning operation. Results: The experimental results showed that the workpiece surface temperature can be sensed and used effectively as an indicator to control the cutting performance and improves the optimization process. Conclusion: Thus, it is possible to increase machine utilization and decrease production cost in an automated manufacturing environment.